Acute Nitrobenzene Poisoning with Severe Methemoglobinemia: ACase Report - Md., Hisham; A, Vijayakumar; N, Rajesh; M.N, Sivakumar (Indian Journal of Pharmacy Practice)
Introduction: Nitrobenzene, an aromatic organic compound used in paints and printing industry. Its toxicity induces methemoglobinemia. Clinical Sequelae: A42 year female patient survived a suicidal consumption of 250ml of 20% Nitrobenzene. On presentation to the hospital, the patient was unconscious and showed typical signs of cyanosis, abnormal arterial blood gas (ABG) showing metabolic acidosis with SpO of 83%, 2 and the arterial blood sample was chocolate brown in colour. The patient suspected of methemoglobinemia showed the formation of 17.7% methemoglobin (normal: 0-2 % of Hb). Management: She underwent supportive treatment and was given 1% methylene blue and 1gm ascorbic acid which acts as an oxygen scavenger. The patient eventually made a complete recovery and the ABG was entirely normalized after 17 days due to intensive treatment. Conclusion: Acute Methemoglobinemia is usually associated with high mortality; hence early identified and aggressive management of poisoning should be attempted. RBC exchange transfusion and hyperbaric oxygen therapy are usually reserved for patients who are resistant to standard treatment.
Keywords: Ascorbic Acid; Cyanosis; Methylene Blue; Nitrobenzene; Methemoglobinemia; ABG